Análise do potencial de transformação de micro e pequenas organizações do terceiro setor em negócios sociais - Tavares, Milca Neves (2018)
This study investigates the potential of third sectors micro and small organizations to become social business, understood here as one that is commitment to the socio-environmental mission and constantly seeks its financial sustainability. Through empirical research, using grounded theory, a framework was constructed to identify the potentialities and opportunities of thirty-two third sectors organizations. It was possible to conclude that there is potential for transformation of these organizations into social business given their commitment to the socioenvironmental mission and the impacted stakeholders and given the business mechanisms that are beginning to be adopted. However, the leader´s profile of these organizations does not show the characteristics of traditional enterprises, it represents a challenge for a transition. This work generates insights for organizations that act on social responsibility or social innovation and seek in partnerships to reduce risks and seize opportunities.